2015
DOI: 10.1111/bph.13218
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐study variability of preclinical in vivo safety studies and translational exposure–QTc relationships – a PKPD meta‐analysis

Abstract: BACKGROUND AND PURPOSEPreclinical cardiovascular safety studies (CVS) have been compared between facilities with respect to their sensitivity to detect drug-induced QTc prolongation (ΔQTc). Little is known about the consistency of quantitative ΔQTc predictions that are relevant for translation to humans. EXPERIMENTAL APPROACHWe derived typical ΔQTc predictions at therapeutic exposure (ΔQTcTHER) with 95% confidence intervals (95%CI) for 3 Kv11.1 (hERG) channel blockers (moxifloxacin, dofetilide and sotalol) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 41 publications
6
28
0
Order By: Relevance
“…In turn, the analysis herein proposed suggests that, for example, the 2.5 % change in the QT interval is equivalent to a median of 10 and 5.85 ms QT-interval prolongation in humans and dogs, respectively. Furthermore, the findings of our analysis are also in agreement with a recently proposed study in which, based on a PK/PD meta-analysis approach, it was found that moxifloxacin concentrations between 2.9 and 5.6 lM induced a typical 4-12 ms prolongation in dogs with a corresponding typical 7-19 ms prolongation in humans [26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In turn, the analysis herein proposed suggests that, for example, the 2.5 % change in the QT interval is equivalent to a median of 10 and 5.85 ms QT-interval prolongation in humans and dogs, respectively. Furthermore, the findings of our analysis are also in agreement with a recently proposed study in which, based on a PK/PD meta-analysis approach, it was found that moxifloxacin concentrations between 2.9 and 5.6 lM induced a typical 4-12 ms prolongation in dogs with a corresponding typical 7-19 ms prolongation in humans [26].…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, in [23] it is mentioned that no cases of TdP in 14,044 patients treated with moxifloxacin were reported. Previous publications [24][25][26] have shown that a model-based paradigm can provide the basis for a translational approach across species. In view of this, preclinical findings as well as the knowledge of the translational relationship between species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Those “system‐ and drug‐specific” translational predictions were externally evaluated using literature data, and compared with “empirical” predictions (from in vivo data alone) (Gotta et al. ) and in silico predictions (from in vitro data alone) (O'Hara et al. ; Mirams et al.…”
Section: Methodsmentioning
confidence: 99%
“…QTc was both in preclinical (Gotta et al. ) and clinical (Jonker et al. ) studies centered to a heart rate of 60 bpm (RR interval of 1000 msec).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation